1999
DOI: 10.1080/000155599750010841
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic Cellulitis in a Child Successfully Treated with Cetirizine

Abstract: Eosinophilic cellulitis was ¢rst described in 1979 by Wells & Smith (1) as a recurrent granulomatous dermatitis with eosinophilia. It is a rare skin condition usually a¡ecting adults and only a few cases have ever been reported in children. CASE REPORT A 12-year-old girl presented with an erythematous, papular, occasionally pruritic eruption covering both her legs. Her main complaint was aesthetic. The rash consisted of grouped red papules 10^15 mm in size. The patient was afebrile and reported no arthralgia o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Exclusive use of antihistamines had 25% of resolution rate in eosinophilic cellulitis [ 53 ]. Cetirizine was preferred, as it inhibits eosinophil and neutrophil chemotaxis, and cetirizine alone gave a quick response and offered prolonged remission in one pediatric case [ 54 ].…”
Section: Clinical Applications In Dermatologic Diseasesmentioning
confidence: 99%
“…Exclusive use of antihistamines had 25% of resolution rate in eosinophilic cellulitis [ 53 ]. Cetirizine was preferred, as it inhibits eosinophil and neutrophil chemotaxis, and cetirizine alone gave a quick response and offered prolonged remission in one pediatric case [ 54 ].…”
Section: Clinical Applications In Dermatologic Diseasesmentioning
confidence: 99%
“…This patient was a 12-year-old girl who developed recurrent pruritic papulonodular lesions of both legs. Cetirizine induced rapid response and permitted prolonged remission for 18 months [ 9 ]. Furthermore, previous studies have demonstrated that cetirizine, a metabolite of hydroxyzine, and levocetirizine inhibit transepidermal migration and chemotaxis of eosinophils [ 10 ].…”
Section: Discussionmentioning
confidence: 99%